2012
DOI: 10.2169/internalmedicine.51.7097
|View full text |Cite
|
Sign up to set email alerts
|

Down-Klinefelter syndrome (48,XXY,+21) in a Child with Congenital Heart Disease: Case Report and Literature Review

Abstract: Congenital heart disease (CHD) is extremely rarely reported in 48, XYY, +21 karyotype. Herein, we reported one case of 48,XYY,+21 karyotype with CHD and reviewed the available literature. The phenotypic characteristics of the 4-month-old child showed the presence of features typical of mongoloid slant. X-ray detection showed the form of heart was corpulent and the bilateral mediastinum was broad. Doppler echocardiogram detection showed atrial septal and ventricular septal defects with patent ductus arteriosus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Among 3550 KS subjects, Swerdlow et al (7) reported that CCD was the specific cause of mortality in five patients (Standardized Mortality Ratio = 7.3). To the best of our knowledge, all cases of CCD in KS (68,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94) are fully reported in the Supplemental Data 1, see section on supplementary data given at the end of this article.…”
Section: Structural and Functional Cardiovascular Abnormalities In Klmentioning
confidence: 99%
“…Among 3550 KS subjects, Swerdlow et al (7) reported that CCD was the specific cause of mortality in five patients (Standardized Mortality Ratio = 7.3). To the best of our knowledge, all cases of CCD in KS (68,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94) are fully reported in the Supplemental Data 1, see section on supplementary data given at the end of this article.…”
Section: Structural and Functional Cardiovascular Abnormalities In Klmentioning
confidence: 99%
“…However, in our case, the parents were very young. From the published cases, we can conclude that the paternal ages are remarkably different in patients with a double aneuploidy of 48,XXY,+21 associated with CHD (Table 1) [713]. The exclusion of advanced maternal age as risk factor for chromosomal non disjunction in the present case suggests the existence of other risk factors.…”
Section: Discussionmentioning
confidence: 55%
“…In a review by Shen et al (2012), of 63 cases of double aneuploidy 48,XXY,+21, only 15% of reports revealed some degree of congenital heart disease. According to our research, there seem to be differences between the frequency of congenital heart disease among patients with Down-Klinefelter and DS, because the incidence of heart disease in patients with DS can reach 60% of cases, according to the literature.…”
Section: Discussionmentioning
confidence: 99%